BENTUK REPETISI LINGUISTIK DALAM AL-QURAN - Nur Faizi; Syamsul Hadi; Thoyyib Thoyyib (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
This study discusses the linguistic forms of repetition that occurs in the Koran. Although there has been much study of repetition (takrâr) in the Koran, this study differs from previous studies because this study is a comprehensive linguistic research in the general frame. This makes the study of the Koran as meterial object on the basis of the Koran is a text language that includes various forms of repetitions (reps). By descriptive-qualitative method, repetition is studied in hierarchical linguistic units contained in the general linguistic forms which includes: the phonological repetition, grammatical repetition, and thematic repetition. This study also shows the types of repetition. The study found the type of phonological repetition include: rhyme, alliteration, assonance; the type of grammatical repetition include: reduplication, repetition of words, phrases, clauses, sentences, and syntax repetition (parallelism); the type of thematic repetition includes paraphrasing.